Răspuns :
a+b=52
a:b=3 rest 8
(scriem teorema impartirii)
d=i*c+r( si inlocuim)
a=b*3+8
3b+8+b=52(am inlocuit in prima relatie:a+b=52)
4b+8=52
4b=52-8
4b=44l:4
b=11
a=52-11
a=41
a:b=3 rest 8
(scriem teorema impartirii)
d=i*c+r( si inlocuim)
a=b*3+8
3b+8+b=52(am inlocuit in prima relatie:a+b=52)
4b+8=52
4b=52-8
4b=44l:4
b=11
a=52-11
a=41
a+b=52
a:b=3 rest8⇒a=3b+8
3b+8+b=52
4b+8=52
4b=52-8
4b=44⇒b=44:4
b=11⇒a=3x11+8
a=33+8
a=41
a:b=3 rest8⇒a=3b+8
3b+8+b=52
4b+8=52
4b=52-8
4b=44⇒b=44:4
b=11⇒a=3x11+8
a=33+8
a=41